2017
DOI: 10.1186/s40249-017-0290-6
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of schistosomiasis transmission in mountainous and hilly regions with an integrated strategy: a longitudinal case study in Sichuan, China

Abstract: BackgroundSchistosomiasis remains a major public health concern in China. Since 2004, an integrated strategy was developed to control the transmission of Schistosoma japonicum in China. However, the long-term effectiveness of this integrated strategy for the interruption of schistosomiasis transmission remains unknown in the mountainous and hilly regions of China until now. This longitudinal study aims to evaluate the effectiveness of the integrated strategy on transmission interruption of schistosomiasis in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In 2004, China implemented an integrated strategy for schistosomiasis control that includes mass treatment and education but also snail control, improved sanitation, and replacement of working bovines with agricultural machinery [16, 17]. This shift has resulted in the elimination of human schistosomiasis cases in formerly endemic communities, as well as the elimination of infected bovines and snails in selected areas [16, 17]. However, it is important to note that most rural endemic communities such as Macanip suffer from long-term poverty as well as disease.…”
Section: Resultsmentioning
confidence: 99%
“…In 2004, China implemented an integrated strategy for schistosomiasis control that includes mass treatment and education but also snail control, improved sanitation, and replacement of working bovines with agricultural machinery [16, 17]. This shift has resulted in the elimination of human schistosomiasis cases in formerly endemic communities, as well as the elimination of infected bovines and snails in selected areas [16, 17]. However, it is important to note that most rural endemic communities such as Macanip suffer from long-term poverty as well as disease.…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore assumed that the successful intervention packages piloted in the marshland and lake regions are not fully suitable for the hilly and mountainous environments in the Sichuan and Yunnan provinces of China [ 36 ]. Although field studies have shown that this new integrated strategy remains effective to control S. japonicum infection in humans and snails in hilly and mountainous endemic foci [ 26 , 27 , 57 ], regionally flexible integrated, intersectoral, and setting-specific control strategies driven by local circumstances and data are needed [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The morbidity control strategy, also known as the conventional strategy, focuses on synchronous chemotherapy for humans and bovines [ 4 ], and the new strategy developed in 2004 intervenes in the transmission pathway of schistosomiasis japonica, mainly including replacement of bovines with machines, prohibition of grazing cattle in the grasslands, improving sanitation, installation of fecal-matter containers on boats, praziquantel drug therapy, snail control, and health education [ 42 ]. This new integrated control strategy has proven to be highly effective to reducing the rate of S. japonicum infection in both humans and the intermediate host snails [ 24 , 26 , 39 , 43 , 46 , 65 , 66 ]. However, the effectiveness of this new integrated strategy varies in previous reports in terms of the implementation in different endemic regions and different local circumstances [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although of less severity then the Yangtze River Basin with respect to schistosomiasis endemicity, the mountainous areas in eastern China are a major problem since the topography impedes large-scale approaches requiring somewhat different strategies than those used elsewhere. Liu et al [ 16 ] report good results from a 10-year longitudinal study evaluating a small-scale approach where an important ingredient is the replacement of bovines with machines. Chemotherapy, snail control and sanitation were also used and information, education and communication (IEC) materials were distributed to each household.…”
Section: All Together Nowmentioning
confidence: 99%